Intertext als Gedenken. Herta Müllers Roman «Der Fuchs war damals schon der Jäger» in Konstellation mit Texten von Günter Grass: [Intertext as Remembrance. Herta Müller’s Novel «Even back then, the Fox was the Hunter» in Constellation with Texts by Günter Grass] (Studia theodisca, 2020)
This article traces intertextual references in Herta Müller’s 1992 novel Even back then, the Fox was the Hunter with Günter Grass’s texts as a dialogical form of remembrance. In conjunction with an excerpt from Günter Grass’s Peeling the Onion, selected passages are examined to show how these texts articulate in exemplary manner a remembrance of experiences of dictatorship, war, and National Socialism. Herta Müller’s and Günter Grass’s texts discuss contemporary historical “collective events” in a special literary conjunction of fiction and memory distinguished from the historical discourse which invokes reality.